The Guarantee Measures of Educational Rights on the Traditional Communities of Southwest Papua - Markus, Dwi P; Mahmudah, Masrifatun; Arya, Surandi Wong; Yati, Sri (International Journal of Law Reconstruction, 2024)
This research aims to know the guarantee measures of educational rights, and analyse its from custom law. This research is empirical study that uses field data as primary data sources. Data collection techniques were carried out from interviews, observation and documentation. The result show that absorption of at least 30% of the budget income and expenditure areas that must be absorbed by education No appropriate target, the spelled out small if compare with budget income and to much expenditure area and must capable to accommodate cost of school for 203 Papuan children. This all based on government programs as well not yet appropriate and take the good target. It should check again on many factors and reason that show many separated Papuan school and different area, distance and difficult geological area which impact to the student and decide not to continue their education including economic factor.